Faktor Yang Mempengaruhi Timbulnya Tuberculosis Limfadenitis di Rumah Sakit Umum Pusat Wahidin Sudirohusodo Pada Tahun 2021-2023 - Andi Dila Cantika Carmelia; Syamsu Rijal; Amrizal Muchtar; Edward Pandu Wiriansya; Andi Masdipa (Wal'afiat Hospital Journal, 2025)
Tuberculosis is a contagious disease caused by the bacterium Mycobacterium tuberculosis. This bacterium primarily affects the lungs, but it can also spread to other organs. One of the most commonly found forms of extrapulmonary tuberculosis is Tuberculous Lymphadenitis, which is a TB infection that affects the lymph nodes, especially in the cervical (neck) region. There are many factors that can contribute to the development of this disease. This study aims to identify the factors that influence the occurrence of Tuberculous Lymphadenitis at Wahidin Sudirohusodo Central General Hospital in Makassar during the period of 2021 to 2023. This quantitative research uses a cross-sectional approach to determine the risk factors—age, gender, nutritional status, history of tuberculosis, history of contact, diabetes mellitus, HIV status, immunization status, and hypertension—associated with the occurrence of Tuberculous Lymphadenitis. Data collection began with identifying TB cases, followed by tracing the associated risk factors that may lead to Tuberculous Lymphadenitis. The study population included all patients diagnosed with Tuberculous Lymphadenitis at Wahidin Sudirohusodo Central General Hospital from January to December in the years 2021–2023. The sampling technique used was quota sampling, a non-probability method based on non-random selection of a specific number or proportion of participants. A total of 422 samples that met the inclusion criteria were included in the study.The results showed that age, gender, nutritional status, diabetes mellitus, hypertension, and BCG immunization had a significant relationship with the incidence of Tuberculous Lymphadenitis. In contrast, history of tuberculosis, HIV status, and history of contact did not show a significant association with the disease.